Rhetorical devices in the language of Shona printed adverts - Mushore, Washington (Unisa Press, 2016)
This article looks at how the language of advertising is designed to maximize its persuasive potential. Semiotic theory will be used in unpacking the meanings of the rhetoric devices in the language of Shona printed advertisements. Rhetoricians recognized that a well-organized advertisement is more convincing or more persuasive than a poorly ordered one. Arguments or benefits of products, services or ideas have to be arranged in the best possible formation if advertisements are to achieve their aims. Since rhetoric is about effective communication, that is, the ability to communicate thoughts with utmost advantage, the basic argument of this article is therefore that the language that advertisers use in their advertisements is something that is carefully designed in order to bait potential customers. Two Shona printed advertisements namely Shumba Super Dust and WaterGuard produced in Zimbabwe will be used as examples.